THE CONCEPTUAL BASIS OF INTEGRATED, ENVIRONMENTALLY FRIENDLY SYSTEM FOR THE PROTECTION OF MAJOR CROPS FROM CYST NEMATODES - A. G. Babich; A. A. Babich (Российский паразитологический журнал, 2016)
Objective of research. To elaborate a framework for integrated protection of agricultural crops from oat, sugar beet, Golden potato, alfalfa and clover nematodes.Materials and methods. The effectiveness of different anti-nematode measures was studied in 1991-2016 in Vinnyza, Kiev, Sumy, Chernigov and other regions of Ukraine. As research material served samples of soil, plants; eggs, larvae, imago; beet, oat, Golden potato, alfalfa and clover cyst nematodes. Preparation of temporary and permanent slides, determination of the species composition of cyst nematodes were carried out by standard methods [3, 6].Results and discussion. The framework of integrated protection of agricultural crops from oat, sugar beet, Golden potato, alfalfa and clover nematodes has been elaborated. To prevent mass reproduction of cyst-forming nematodes, the saturation of crop rotations with host plants must not exceed 40% — with cereal grains; 20% — beet and oilseed Brassica (canola, radish, and mustard); 15% — potatoes; 20% — perennial legumes. Involvement of crops and green manure in the by-products cycle has a positive effect on the level of soil fertility and activation of life activity of natural antagonists of Heteroderidae.